Engagerade ungdomar - Dahl, Camilla; Karlsson, Camilla (2008)
The consumption and energy use in today's society contributes to the on-going climate change that creates a debt of life quality for future generations (www, DN, 2007, a). The resources that are used by humans exceed by far what is sustainable (www, Regeringen, 2007, a).